A Study of Anxiety in Epileptic People Attending Out-Patient Department of Psychiatry, Nepal Medical College Teaching Hospital - Singh, PM; Khadka, S; Chhetri, A (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Epilepsy is the most common chronic neurological disease in the general population and affects approximately 1% of the population in the United States. Anxiety disorders are common co morbidity among patients with epilepsy. Incidence of anxiety was found to be 16.7% in patients with epilepsy. This study has tried to evaluate the anxiety disorder in patients with epilepsy attending outpatient department of Nepal Medical College. Objective: To estimate the prevalence of anxiety in outpatients with epilepsy and the sociodemographicprofiles of patients with epilepsy. Methods: It is a descriptive cross-sectional study. The sample comprised of 55 outpatients with epilepsy attending Psychiatry department of Nepal Medical College Teaching Hospital. Informed consent was taken and semi- structured proforma was filled with adequate information. Diagnosis was based on ICD-10 DCR and severity was assessed using Hospital Anxiety and Depression Scale (HADS). Data was evaluated with SPSS 16 and appropriate statistical tools were applied. Results: The study found that a great number of epileptic patients were suffering from comorbidanxiety disorder (36.36%). Also married patients had higher anxiety disorder (57.69%), thus, showed a significant relation based on marital status and anxiety in epileptic patients. Conclusion: Anxiety disorders are common in people with epilepsy. Increased awareness of the clinical presentations of anxiety disorders should be initiated for securing the mental health and quality of life in people with epilepsy.